2003
DOI: 10.1023/a:1024020124397
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Seeking to identify conditions that support newly implemented evidence-based practices, this case study examined an implementation in which an existing agency was invited to move into the neighboring county to introduce its "housing first" practice with seriously mentally ill homeless adults. Using a constructivist methodology to elicit the narratives of key actors and observers about the implementation and its attendant controversy, this study found three issues at the core of actors' experiences: mode of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Similarly, in a study introducing innovation for homeless people with mental health problems, the mode of presentation, use of an outside agency, and the questioned uniqueness of the new practice were found to be as important as the intervention itself [13]. Most importantly, as Proctor et al .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study introducing innovation for homeless people with mental health problems, the mode of presentation, use of an outside agency, and the questioned uniqueness of the new practice were found to be as important as the intervention itself [13]. Most importantly, as Proctor et al .…”
Section: Introductionmentioning
confidence: 99%
“…This includes not only choosing type of living situation but also deciding whether to take psychiatric medications or abstain from drugs and alcohol (Salyers & Tsemberis, 2007). This approach, which openly embraces harm reduction, has been met with past skepticism (Felton, 2003), yet research has overwhelmingly demonstrated that PHF consumers are able to maintain independent apartment living and manage multiple health conditions when provided with flexible supports (Pearson et al, 2009; Substance Abuse and Mental Health Administration [SAMHSA], 2007; Tsemberis et al, 2004). Despite working with the same target population, PHF providers work in organizational settings that reflect these structural and philosophical differences from TF program models.…”
mentioning
confidence: 99%
“…The most common practice settings identified were primary healthcare (n = 10) [42,44,53,59-62,64,65,82], followed by post-graduate educational settings (n = 7) [39-41,43,45,65,81], and mental health clinical environments (n = 5) [50,52,58,78,80] (Table 3). Nursing was the professional group most frequently targeted in the papers (20 of 35 included studies), alone [42,43,47,53,55,60-62,77], or along with physicians [64,82], patients [44], or interdisciplinary teams [38,39,48,51,57,65,76,79]. Psychologists/psychiatrists was another identified group (n = 5) [50,52,58,78,80].…”
Section: Resultsmentioning
confidence: 99%
“…The papers [46-52,76,79] in this theme reported findings from literature reviews exploring the meaning of evidence and the epistemology of research and practice. Papers in this theme recognized that there may be various definitions of ‘knowledge’ and ‘knowledge creation’ which may vary depending upon the theoretical lens used to explore the applications of knowledge in clinical practice.…”
Section: Resultsmentioning
confidence: 99%